Kesenjangan Norma Hukum Perdata dan Praktik Sosial dalam Perjanjian Bagi Hasil Pertanian di Desa Tranjang - Melani Dwi Andini; Ucuk Agiyanto; Aries Isnandar (Fakultas Hukum Universitas Riau, 2026)
This study aims to analyze the gap between civil law norms and social practices in the implementation of agricultural sharecropping agreements between landowners and cultivators in Tranjang Village, Siman District, Ponorogo Regency. The study employs a juridical- empirical approach by combining normative legal analysis of statutory provisions with empirical field research through observation and in- depth interviews with 15 informants consisting of landowners, cultivators, and village authorities. The findings reveal that most sharecropping agreements in Tranjang Village are conducted verbally based on mutual trust between landowners and cultivators, without written contracts or official authorization by village authorities. Such practices are rooted in agrarian social values emphasizing kinship and mutual cooperation, but do not fully comply with formal legal standards stipulated in Law No. 2 of 1960. This gap is caused by low legal awareness, complex and costly administrative procedures, social and cultural values that prioritize trust over formal rules, and the passive role of village government in facilitating contract registration. The study recommends revitalizing the role of village authorities in facilitating agricultural contracts through the provision of simple contract formats that can be legalized quickly and affordably, legal socialization with participatory local cultural approaches, and revision of Law No. 2 of 1960 to be more adaptive to the social realities of agrarian communities while ensuring legal protection for cultivators.